THE EFFECT OF HATHA YOGA ON DYSMENORRHOEA PAIN IN ADOLESCENT PRINCIPLE - Ummi Sa'adah; Kholisotin K; Zainal Munir; Handono FR; Abdul Hamid Wahid (Journal of Maternity Care and Reproductive Health, 2019)
Dysmenorrhea is pain during menstruation caused by muscle contraction and imbalance of the hormone progesterone in the blood. One of the non-pharmacological treatments is Hatha yoga therapy, which is a type of relaxation technique that can reduce pain intensity by relaxing skeletal muscles. This study was purposed to determine the effect of Hatha Yoga Therapy on Dysmenorrhoea Pain in Adolescents at Darul Falah Islamic Boarding School. The design of this study was the "Quasy experiment" study using "group non-equivalent controls" which were divided into experimental groups and control groups. The study was conducted at Darul Falah Islamic Boarding School, the number of 76 adolescents was taken using a simple random sampling technique. The measuring instrument used is the observation sheet. Hatha yoga intervention is carried out for 1 month with a frequency of 2 times for 40 minutes. The analysis used univariate and bivariate analysis using Mann Whitney and Wilcoxon. This study found a decrease in the intensity of dysmenorrhea pain in the experimental group after being given hatha yoga (p-value 0,000 <α 0,05) whereas in the control group P-value = 0,102 (p> 0,05). The conclusion is that there is the influence of Hatha Yoga on the pain of dysmenorrhea in young women.Keywords: Dysmenorrhea, hatha yoga.